Evaluation of some genotypes of maize (Zea mays L.) for tolerance to drought in Northern Ghana - Bawa, A; Addai, I K; Kugbe, J X (Research in Plant Biology, 2015)
Pot and field studies were conducted to screen twenty five genotypes of maize for tolerance to drought in Northern Ghana during the 2012 and 2013 cropping seasons. For the pot studies, seeds were planted in June 2012 in 0.20 m × 0.30 m surface pots arranged in rows on a platform with a distance of 1 m between the rows. After emergence, 2 l of water was applied to the plants in each pot, once every week for the non-stressed treatments (control). To mimic drought conditions, the same amount of water was applied, but once every two weeks to the stress treatments. Treatments were replicated three times in a completely randomized design. For the field study, genotypes were evaluated on single-row plots of three replicates, in a randomized complete block design. Plants designated as control were planted at the normal and usual time of planting of maize in the study area (July 2013), whilst those subjected to water-stressed treatments were planted late (six weeks later) to ensure that their growth period coincides with the drought period. Results on yield and agronomic parameters showed that three of the genotypes (GUMA03-OB, KOBN03-OB and SISF03-OB) were highly tolerant to drought, whilst eleven genotypes (NYAZ04-W, TAAN04, TAIS03, TZE-Y-DT-STR-C4, NYSW03-Y, NYIA03, DORKE SR, TZE-W-DT-STR-C4, NYFA04, KOBN04-R, and CHMA04) were moderately tolerant. The rest of the genotypes showed moderate to high levels of drought susceptibility. Drought plant rating and anthesis-silking interval (ASI) were significantly reduced when plants were watered throughout the experimental period (control) as compared to those stressed. However, grain yield, plant height, ear height, days to 50% anthesis, days to 50% silking, leaf area, chlorophyll content, fresh and dry shoot weight and root length were significantly higher (P < 0.05) for the non-stressed plants as compared to those subjected to water stress. In drought-prone geographical areas like Northern Ghana, genotypes such as GUMA03-OB, KOBN03-OB and SISF03-OB or their crosses can be used for increased grain yield.